The contribution of Enrico C. Vigliani (1907-1992) to the international development of Occupational Medicine and Industrial Hygiene / Il contributo di Enrico C. Vigliani (1907-1992) allo sviluppo internazionale della medicina del lavoro e dell’igiene ... - Riva, Michele Augusto; Carnevale, Francesco; D'Orso, Marco Italo; Iavicoli, Sergio; Bertazzi, Pier Alberto; Cesana, Giancarlo (La Medicina del Lavoro, 2012)
Summary Background: One of the last century’s greatest personalities in Occupational Medicine was Enrico Carlo Vigliani (1907-1992), director of the “Clinica del Lavoro” in Milan (1942-1977), editor-in-chief of “La Medicina del Lavoro” (1942-1991), Secretary-Treasurer and then President of the “Permanent Commission and International Association on Occupational Health” (1957-1981), the original nucleus of the ICOH. Objectives: The 20th anniversary of his death provides us with the opportunity to discuss the role of this brilliant scholar in the international development of Occupational Medicine and Industrial Hygiene. Methods: A comprehensive analysis of Vigliani’s scientific works was conducted. In addition, his close collaborators and pupils were interviewed. Results: In the 1930s, as a young doctor, Vigliani, first in the world, demonstrated the effect of lead on porphyrin metabolism. Afterwards he conducted pioneering studies on occupational oncology (benzene-induced leukaemia, bladder cancer due to aromatic amines, asbestos-related tumours), pathogenesis of silicosis, encephalopathy in carbon disulfide poisoning, byssinosis and metal fume fever, so influencing international research and the implementation of preventive measures against these conditions. Vigliani’s scientific authority was widely recognized internationally, as confirmed by his role in ICOH. During his period of active service, the Commission developed from an academic institution to a more open association, substantially increasing its membership. Furthermore, he contributed to establishing subcommittees devoted to specific topics (now called “scientific committees”), one of the strengths of the present Commission. Conclusions: Vigliani’s contribution to the development of Occupational Health may be considered as an expression of his genial eclecticism which ranged from clinical medicine to the environment. Riassunto «Il contributo di Enrico C. Vigliani (1907-1992) allo sviluppo internazionale della medicina del lavoro e dell’igiene industriale». Introduzione: Enrico Carlo Vigliani (1907-1992) è stato una delle personalità più rilevanti nel campo della Medicina del Lavoro nello scorso secolo: direttore della “Clinica del Lavoro” di Milano (1942-1977) e della rivista “La Medicina del Lavoro” (1942-1991), Segretario-Tesoriere e Presidente della “Permanent Commission and International Association on Occupational Health” (1957-1981), nucleo originario dell’ICOH. Obiettivi: Il ventesimo anniversario della sua scomparsa offre l’opportunità per definire il ruolo avuto da questo illustre scienziato nello sviluppo internazionale della medicina del lavoro e dell’igiene industriale. Metodi: Oltre ad un’analisi dettagliata dei lavori scientifici di Vigliani, sono state condotte interviste ai suoi più stretti collaboratori ed allievi. Risultati: Negli anni Trenta, Vigliani, primo al mondo, dimostrò l’effetto del piombo sul metabolismo porfirinico. Successivamente condusse studi pioneristici nel campo dell’oncologia professionale (leucemia da benzene, tumori vescicali da amine aromatiche, tumori connessi all’amianto) e nel campo della patogenesi della silicosi, dell’encefalopatia nell’intossicazione da disolfuro di carbonio, della bissinosi e della “febbre da fumi metallici”, influenzando così la ricerca scientifica internazionale su queste tematiche e l’implementazione di misure preventive nei confronti di queste patologie. L’autorevolezza scientifica di Vigliani era ampiamente riconosciuta all’estero, come confermato dal suo ruolo nell’ICOH. Durante il suo mandato, la Commissione si trasformò da istituzione accademica a vera e propria associazione medica, aumentando significativamente il numero di membri. Inoltre Vigliani contribuì a fondare i comitati scientifici dell’ICOH, uno dei suoi attuali punti di forza. Conclusione: Il contributo di Vigliani allo sviluppo della medicina del lavoro può essere considerato espressione del suo geniale eclettismo che spaziava dalla clinica alle tematiche ambientali.